Facteurs Des Constituants De la reproduction des ovins - Doghmane, Ayoub (My University, 2020)
The present study is a contribution to the evaluation of the reproductive potential of breeds . The good control of the reproductive parameters of this breed allows a better productivity. Reproduction is influenced by different external factors represented the environment, diet, method and time of struggle and internal represented by the genetic potential. The study is carried out at the level of the pilot farm , sheep flock is existing there composed of 349 heads. In the last part we evaluated the reproductive parameters represented by the fertility, the prolificacy and the mortality of the lambs from the data collected on the herd, then we analyze the state of places, finally we try to raise the constraints and that in the perspective of developing production. From the results obtained in the breeding parameters between the years 2020 and 2019 we obtained: A fertility rate of 89% and 91% A prolificity rate of 105% A fertility rate of 91% and 94% A mortality rate of 2% and 14%
Keywords: wrestling; sheep; fertility; prolificacy; fertility.